(untitled) (Fiep Bulletin - online, 2025)
The research Characterization of the Physical Education Class and Motor Engagement Time in the Schools of the Valley of Mexico, within the framework of the New Mexican School allowed measuring the Motor Engagement Time (MET) of the Physical Education classes and the actions and/or teaching strategies used by teachers that result in these results. The theoretical support supports the importance of Motor Engagement Time in the Physical Education session concerning motor development, health promotion, and prevention of non-contagious diseases, among others. As part of the methodology, 36 Physical Education classes were observed in three Physical Education supervisions in the Valley of Mexico in two moments, with a time interval of between five and six weeks between each one, 72 observations in total. The sample was obtained through simple random selection. A recording sheet from García and Ruiz (2017) and a video recording were used for observation. The results are presented quantitatively and qualitatively. The teaching strategies that allowed Physical Education teachers to achieve the best MET in the class and the actions that considerably reduce it are specified.